Selective Oxidation of Sulfides to Sulfoxides Using Modified Keggin Heteropolyacids as Catalyst - Vazquez, Patricia Graciela (2014)
The use of modified Keggin phosphomolybdic heteropolyacids (HPA) (V and Al) as catalysts in the selective oxidation of sulfides to the corresponding sulfoxides is reported. Excellent yields were obtained (13 examples: 79%-95%), using 35% (w/v) aqueous hydrogen peroxide as oxidant, and acetonitrile as solvent at 25°C. The relationship between the electron densities of the sulfur atoms, which was estimated by molecular theoretical calculations, and the oxidative relativities of the sulfur-containing compounds was also investigated. The results indicate that the time for 100% conversion decreases with an increase in electron density.